PERAN SUPERVISI PENDIDIKAN DALAM MEMBANGUN BUDAYA BELAJAR YANG BERKELANJUTAN DI LINGKUNGAN BELAJAR - Arif, Isnan; Syafriyanda, Syafriyanda; Ramadhan, Syahrudi (Universitas Riau, 2024)
Educational supervision has a strategic role in creating a sustainable learning culture in the learning environment. This culture refers to a dynamic, collaborative, and adaptive learning process to the changing times, with the aim of supporting lifelong learning. This article reviews the literature on the role of educational supervision, focusing on its impact on improving the quality of learning and fostering a future-oriented learning culture. This study uses a literature study method. Literature study is a study in the context of collecting data or information through various library reading materials, such as books, journals or articles, historical records and so on. The conclusion of the literature study carried out to obtain the results of supervision not only functions as an evaluation tool, but also as a means of coaching and mentoring that supports teachers to continue learning and developing. With the right supervision, a culture of continuous learning will be built among teachers and students, where teachers are encouraged to always innovate, improve their competencies, and work together with their peers.